Patient safety culture in Slovenian out-of-hours primary care clinics - Klemenc-Ketiš Zalika; Deilkås Ellen Tveter; Hofoss Dag; Bondevik Gunnar Tschudi (Sciendo, 2017)
Patient safety culture is a concept which describes how leader and staff interaction, attitudes, routines and practices protect patients from adverse events in healthcare. We aimed to investigate patient safety culture in Slovenian out-of-hours health care (OOHC) clinics, and determine the possible factors that might be associated with it.